First report of Burkholderia gladioli causing bacterial panicle blight of rice in Malaysia - Md Zali, Adam Zafdri; Ja'afar, Yasmin; Paramisparan, Karthik; Ismail, Siti Izera; Saad, Norsazilawati; Mohd Hata, Erneeza; Md Hatta, Muhammad Asyraf; Ismail, Mohd Razi; Yusof, Mohd Termizi; Zulperi, Dzarifah (American Phytopathological, 2022)
Rice (Oryza sativa) is a staple food for most of the world's populations, particularly in Asia (Gumma et al. 2011). The rice sector provides Malaysians with a food supply, food sufficiency, and income for growers (Man et al. 2009). From January to February 2022, panicle samples showing symptoms of bacterial panicle blight (BPB) disease, including reddish-brown, linear lesions with indistinct margins on flag-leaf sheaths and blighted, upright, grayish straw-colored florets with sterile and aborted grains on panicles were collected in granary areas in Sekinchan, Selangor, Malaysia with 90% disease incidence in fields. Surface-sterilization of infected leaf tissue was performed using 75% ethanol and 1% sodium hypochlorite, followed by rinsing three times in sterilized water. Leaf tissue was macerated in sterilized water and aliquots were spread on King's B agar medium, then cultured for 24 h to 48 h at 35 °C. All isolated bacteria were Gram-negative rods, positive for catalase and gelatinase but negative for indole, oxidase and hydrogen sulfide (H2S), and utilized sucrose, inositol, mannitol, glucose, and citrate. Colonies were circular and smooth-margined, producing a diffusible yellowish-green pigment on King's B agar medium, which are characteristics of Burkholderia species (Keith et al. 2005). Five representative isolates (UPMBG7, UPMBG8, UPMBG9, UPMBG15, UPMBG17) were selected for molecular and pathogenicity tests. PCR using specific primers targeting the gyrB gene for molecular characterization was performed, and the ∼470 bp amplicons were sequenced (Maeda et al. 2006) and deposited in GenBank (OM824438 to OM824442). A BLASTn analysis revealed that the five isolates were 99% identical to the B. gladioli reference strains MAFF 302533, GRBB15041, and LMG19584 in GenBank (AB190628, KX638432, and AB220898). A phylogenetic tree using Maximum-likelihood analysis of the gyrB gene sequences showed that the five isolates were 99% identical to B. gladioli reference strains (AB190628, KX638432, and AB220898). To verify the identification of these isolates, the 16S rDNA gene was amplified using 16SF/16SR primers (Ramachandran et al. 2021), producing ~1,400 bp amplicons. The resulting sequences of the five isolates (OM869953 to OM869957) were 98% identical to the reference strains of B. gladioli (NR113629 and NR117553). To confirm pathogenicity, 10 ml suspensions of the five isolates at of 108 CFU/ml were inoculated into the panicles and crowns of 75-day-old rice seedlings of local rice varieties MR269 and MR219 grown in a glasshouse with temperatures ranging from 37 °C to 41 °C (Nandakumar et al. 2009). Control rice seedlings were inoculated with sterilized water. All isolates produced BPB disease symptoms like those originally found in the rice fields at four weeks after inoculation. Control seedlings remained asymptomatic. To fulfill Koch's postulates, the bacteria were reisolated from symptomatic panicles and were confirmed as B. gladioli by sequence analysis of the gyrB and 16S rDNA genes. To our knowledge, this is the first report of B. gladioli causing BPB disease of rice in Malaysia. Since BPB disease causes a significant threat to the rice industry, it is crucial to investigate the diversity of this destructive pathogen for effective disease management strategies in Malaysia.